PROFIL KOMUNIKASI MATEMATIKA TERTULIS DALAM PEMECAHAN MASALAH MATEMATIKA DI SMP DITINJAU DARI KEMAMPUAN MATEMATIKA - Arezqi Tunggal Asmana; Nur Hidayati Laili; Aan Andri Ardiyansah (INSPIRAMATIKA, 2018)
This research aims to describe the profile of written mathematics communication in the mathematics problems solving of SMP in terms of the mathematics ability. This research is a qualitative research because the main data about the accuracy, completeness, and fluency of written mathematics communication in the form of written words. Subjects consisted of one student with high, medium, and low mathematics ability. The results of research indicate that the accuracy of written mathematics communication of students with high and medium mathematics ability is equally accurate for any information submitted. The accuracy of written mathematics communication of students with low mathematics ability is accurate to write the things that are known and asked and use rule. The completeness of written mathematics communication of students with high mathematics ability is complete for any information submitted. The completeness of written mathematics communication of students with medium mathematics ability is complete for information submitted except calculation. The completeness of written mathematics communication of students with low mathematics ability is complete for information submitted except for drawing/sketching and performing calculations. The fluency of written mathematics communication students with high and medium mathematics ability is equally fluent. The fluency of written mathematics communication students with low mathematics ability is not fluent.